228Ra in cow's milk from an anomalous region of Pernambuco-Brazil. Issue 3 (4th May 2019) - Miguel da Silva, Cleomacio; Eduardo de Oliveira Costa Júnior, Carlos
ABSTRACT: The counties of Pedra and Venturosa have one of the largest natural radioactive occurrences of Brazil. The large farms producing milk in the state of Pernambuco are located in these counties. The forage plants cultivated on those farms have high concentrations of 228 Ra, a naturally occurring descending radionuclide from the 232 Th series. The 228 Ra is transferred to the forage plants, and once ingested by the lactating cow, this radionuclide is rapidly transferred to the milk. Thus, milk intake is an important route for 228 Ra of incorporation by the human consumer and may induce the appearance of bone sarcoma. Accordingly, the aim of the present study was to determine the concentrations of 228 Ra in milk produced in the Pedra and Venturosa farms, in order to estimate the risk of ingestion in the local population. The 228 Ra was determined by actin-228 ( 228 Ac) using the radiochemical technique of barium sulphate precipitate (BaSO4 ). The milk samples had concentrations of 228 Ra ranging from 61 to 1338 mBq.l −1, which corresponded to the cumulative equivalent dose ranging from 0.04 to 0.1 Sv. Although the doses were low, regulatory and protective measures should be taken to study the radiotoxic effects of 228 Ra in subjects in the public.